Improving the Cognitive Learning Outcomes of Class XI Students through The Use of Quizizz on Biodiversity at SMAN 93 Jakarta - Dwi Indriani; Aris Munandar (Universitas Lambung Mangkurat, 2023)
This study aims to find out whether there is a difference in the average learning outcomes of class XI students on the subject of Biodiversity at SMAN 93 Jakarta. The method used is a quasi-experimental design with a pretest post-test control group. Sampling in this study uses a purposive sampling technique. The samples in this study were class XI-5 as the control class and XI-6 as the experimental class with a total of 33 students in each class. The data analysis technique in this study is divided into three, namely the instrument test which consists of a validity test and a reliability test. Then the analysis prerequisite test consists of the normality test and homogeneity test as well as the data analysis test, the t-test of two independent samples. The results of the validity test showed that 20 multiple-choice questions compiled based on Anderson & Krathwohl's taxonomy were valid and had a high level of reliability. Then the results of the normality test show that all data is normally distributed and homogeneous. The results of the t-test of two independent samples show the value of Sig. (2-tailed) of 0.000 <0.05 which means H0 is rejected and Ha is accepted. So it can be concluded that there is a difference in the average value between the experimental class and the control class.Â